Project Management (IntechOpen, 2024)
This professional reference book provides a comprehensive overview of project and program management (PProM), capturing recent advancements and current PProM trends. It is a useful reference for educators, engineers, scientists, and researchers in the fields of PProM. The book discusses PProM fundamentals, common practices and approaches, recent advancements, and current trends of modern PProM using technology enablers from the fourth and fifth industrial revolutions (IRs 4. 0 and 5. 0), such as machine learning, artificial intelligence, and big data analytics.